KONTRADIKSI YURISPRUDENSI KOMPETENSI ABSOLUT PENGADILAN AGAMA DALAM MENYELESAIKAN SENGKETA PERBANKAN SYARIAH - Reni Dwi Puspitasari (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
Contradictions Religious Court jurisprudence absolute competence in resolving disputes sticking Islamic banking since the advent of Law No. 21 of 2008 which includes choice of forum for dispute resolution litigation Islamic economy. This triggers legal uncertainty morning the parties. This contradiction is related to the question of the substantive law and procedural law as well as the politics of government laws as proposer is still influenced by the paradigm of colonial law and New Order. In fact, the legal political government is the policy of the law (legal policy) to be implemented at the national, among others, is in the development of laws that core law-making and reform of legal materials that are considered not relevant or appropriate to the needs of the creation of the law. Thus, the government proposal was passed that has hurt the national consensus, because article 55 (2) of Law No. 21 Year 2008 opened the space to settling disputes resolved under the laws of the colonial Dutch government that no longer fit with the culture of Indonesian culture. In addition, the government proposal was passed it was too much to interfere with the judicial realm, for the settlement of Islamic economy had previously been given to the Religious Courts by Law No. 3 of 2006.Keywords: Jurisprudence, Absolut, Islamic Banking